If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y = -7 * 7 + -35 Multiply -7 * 7 7y = -49 + -35 Combine like terms: -49 + -35 = -84 7y = -84 Solving 7y = -84 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '7'. y = -12 Simplifying y = -12
| 3b^2-b-14=0 | | 20x+10=60 | | 2x+3.4=2x+3.4 | | 3(2x-4)-4x=16 | | 2(0)+(y)-6(0)=30 | | -2x+7=12x-6 | | -11+x=7x+5 | | 0=a^2+14a+36 | | 2y^2+7=5 | | 3=3x-6x^2 | | 17-(4-6z)+4=21 | | 2x^2+10-6=0 | | 3a=15+3 | | x/136=1.5 | | 7x-15=36 | | (2k+1)=5 | | r+n=12.5 | | 3n^2-4=26 | | (5t^2-t+2)+(-4t^2+3t+7)= | | 14b+63= | | 9y^2-8+4y^2+9= | | 151=X-13 | | 6x-5=8x+9 | | 2x+3x+1+2=26 | | (x-2)/x=0.88 | | m^2+6m-31=0 | | 2x=8-5 | | 3/X-(1/2x)=1/4 | | r+11+8r=229 | | 5t^2-t= | | -4x-0.5=29.5 | | 4a-6+a=4+a+2 |